2014
DOI: 10.1021/np500219a
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes Are Hidden Producers of Maytansine in Putterlickia Roots

Abstract: Several recent studies have lent evidence to the fact that certain so-called plant metabolites are actually biosynthesized by associated microorganisms. In this work, we show that the original source organism(s) responsible for the biosynthesis of the important anticancer and cytotoxic compound maytansine is the endophytic bacterial community harbored specifically within the roots of Putterlickia verrucosa and P. retrospinosa plants. Evaluation of the root endophytic community by chemical characterization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 41 publications
0
56
0
Order By: Relevance
“…For example, we used a combination of high-performance liquid chromatography-high-resolution mass spectrometry and MALDI-HRMS imaging to reveal that specific potent endophytic bacteria harbored in Cannabis sativa L. plants use quorum quenching as a possible antivirulence strategy to disrupt the cell-to-cell quorum-sensing signals in the biosensor strain, Chromobacterium violaceum [33]. More recently, using a similar approach, we revealed that the potent anticancer and cytotoxic compound maytansine is biosynthesized by the root-associated endophytic microorganisms of Putterlickia plants and is then further localized, typically within the root cortex, for a variety of ecological functions [34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we used a combination of high-performance liquid chromatography-high-resolution mass spectrometry and MALDI-HRMS imaging to reveal that specific potent endophytic bacteria harbored in Cannabis sativa L. plants use quorum quenching as a possible antivirulence strategy to disrupt the cell-to-cell quorum-sensing signals in the biosensor strain, Chromobacterium violaceum [33]. More recently, using a similar approach, we revealed that the potent anticancer and cytotoxic compound maytansine is biosynthesized by the root-associated endophytic microorganisms of Putterlickia plants and is then further localized, typically within the root cortex, for a variety of ecological functions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Following the approval of brentuximab vedotin mentioned above, a second antibody–drug conjugate (ADC) was approved recently, namely, ado-tratuzamab emtansine, which is based in part on the natural product maytansine, and used for patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (5, 6, 13, 14). While initially reported as deriving from a plant, it appears that maytansine is actually of bacterial endophyte origin (15). There are a relatively large number of natural products and their derivatives (inclusive of ADCs) currently in clinical trials as potential new oncolytic agents (5, 6, 14), so further new drugs of this type from a taxonomically varied range of organisms should reach the market.…”
mentioning
confidence: 99%
“…This molecule would subsequently be taken up from the plant’s rhizosphere and modified to produce maytansine by transesterification. In recent excellent work by the Spiteller group, in a paper in 2014, working with a Putterlickia species (one of the first plants from which maytansine was isolated), demonstrated that microbes in the plant’s rhizosphere were the source of maytansine, without any plant involvement (Kusari et al, 2014). …”
Section: Plant-sourced Compounds and Microbesmentioning
confidence: 99%